PERAN UNICEF DALAM MENANGANI KASUS PERNIKAHAN ANAK DI BAWAH UMUR DI INDIA - ", Asmarita; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explain about the role of United Nations Children fund (UNICE)F in preventing child marriage in India. Child Marriage has been part of the fabric social community. This research focus on program that had been made against child marriage.One of Human Right’s issues is Child marriage was appointed writer. Child Marriage is one of part of the Human Right’s issues is being in the spotlight, both in the national and international community. Marriage before the age of 18 is a fundamental human rights violation. Child Marriage has a devastating impact on girls, such as limitless education, limited employment prospects, live in poverty and experience domestic violence. This research theoretically has built with pluralism perspective on International Relations and supported by international organization theories, and also the concept of the role.Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is about UNICEF’s role to control child marriage in India. Researcher has formulated an answer-hypothesis which reveals the fact that the role of UNICEF against child marriage in India is helping India Goverment in social, education, and law. Keywords : United Nations Children Fund, Child Marriage,Human Right, India